A single presumptive deworming may not suffice to reduce the burden of intestinal parasitic infections during pregnancy in rural Amhara, Ethiopia - Kalkidan Yibeltal; Firehiwot Workneh; Nebiyou Fasil; Estifanos Baye; Yunhee Kang; Workagegnhu Tarekegn Kidane; Sitota Tsegaye; Yoseph Yemane Berhane; Bethlehem Haymanot; Ingrid E. Olson; Mulatu Melese Derebe; Rose L. Molina; et al. (BMC Research Notes)
Abstract Objective This study aimed to assess the prevalence of intestinal parasitic infections among pregnant women in the third trimester who received prior presumptive deworming in 12 health centers in the Amhara region, Ethiopia. This sub-study was part of the parent Enhancing Nutrition and Antenatal Infection Treatment (ENAT) study; a randomized clinical effectiveness study conducted to determine the effectiveness of packages of antenatal interventions to enhance maternal nutrition and infection management on birth outcomes. Results Three hundred fifty women provided a stool sample in their 3rd trimester for screening using wet mount microscopy. All women had previously received 500 mg of presumptive mebendazole in the 2nd trimester. One in three women (109/350, 31.0%) were found to have a parasitic stool infection after prior deworming and 15% of women reported gastrointestinal symptoms. The most common infections were Giardia lamblia (n = 43, 37.4%), Entamoeba histolytica (n = 40, 34.8%), and Hookworm (n = 25, 21.7%). Six mothers had co-infections with at least two parasites with trophozoites of Giardia lamblia and Entamoeba histolytica co-infection being dominant.